2009
DOI: 10.3390/molecules14030979
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids with Gastroprotective Activity

Abstract: Peptic ulcers are a common disorder of the entire gastrointestinal tract that occurs mainly in the stomach and the proximal duodenum. This disease is multifactorial and its treatment faces great difficulties due to the limited effectiveness and severe side effects of the currently available drugs. The use of natural products for the prevention and treatment of different pathologies is continuously expanding throughout the world. This is particularly true with regards to flavonoids, which represent a highly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(138 citation statements)
references
References 71 publications
(63 reference statements)
8
130
0
Order By: Relevance
“…However, the decrease of lipid peroxidation mediated oxidative stress may be a potential and effective strategy for the prevention and treatment of peptic ulcer [15]. The present study affirmed the finding of [68,69], who reported that VVE and/or RAN significantly decreased MDA levels in injured gastric and duodenal ulcer due to its antioxidant mechanism, which manifested by the presence of different phytochemical antioxidant components.…”
Section: Discussionsupporting
confidence: 89%
“…However, the decrease of lipid peroxidation mediated oxidative stress may be a potential and effective strategy for the prevention and treatment of peptic ulcer [15]. The present study affirmed the finding of [68,69], who reported that VVE and/or RAN significantly decreased MDA levels in injured gastric and duodenal ulcer due to its antioxidant mechanism, which manifested by the presence of different phytochemical antioxidant components.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest that the unique blend of baicalin and catechin is well-tolerated by the gastrointestinal mucosa in rats and may presumably be well tolerated in humans. In this regard, UP446 is consistent with the reports of other flavonoids, for instance garcinol, rutin and quercetin, shown to either be gastro protective or have been used for the treatment of gastric ulcerations [23,29]. This study also showed that no adverse change in clinical chemistry parameters were observed in male or female rats treated with UP446.…”
Section: Discussionsupporting
confidence: 88%
“…A study conducted in Siqueira et al (2012), had reported the role of terpinoids in the prevention of ulcer and the healing of existing ulcers. The role of flavonoids in gastroprotection cannot be over ruled (Mota et al, 2009;Hussaini et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several conventional antiulcer drugs used in treating gastrointestinal tract disorders, particularly gastric, peptic and duodenal ulcers; these drugs are not in most cases affordable to the ordinary individual giving their high cost and worse of all they come with adverse effects such as arrhythmias, impotence, gynaecomastia and haematopoietic changes (Mota et al, 2009). In view of this, there is the need to seek alternative drugs which are affordable, relatively safe, readily available and acceptable by the majority of the population.…”
Section: Introductionmentioning
confidence: 99%